UGC Guidelines for Internship / Research Internship for Under Graduate Students, 2024 - Dr. H M Naveen (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The NEP-2020 envisions that, research and innovation are two inherent aspects of quality education by HEIs. The Social needs of our country can only be addressed by a strong knowledge, skills and research-oriented higher education system. In accordance with the NEP-2020, the UGC has framed a new student- centric curriculum framework for undergraduate programmes with an emphasis on internship/research internship. A prime aspect of this internship course is induction of students into actual work situation. It requires to participate in a work experience or professional activity under the supervision of external expert. Internship includes working with government or private organizations, HEIs, universities, R&D Labs, NGOs, business organizations, local industry and similar other organizations for providing opportunities to students for active engagement in on-site experiential learning. An internship is gaining first-hand experience by an individual besides comprehending the way of working in an organization. These programmes shall be organized in such a way that benefits the research intern as well as the internship providing organization. Keeping this in view, the UGC has framed these Guidelines for Internship/Research Internship for Undergraduate Students. These guidelines enlighten the interns as well as the organizations about the Objective of Internship, Internship Categories, Structure, Academic Credentials & Monitoring of Internship, Role of Internship providing Organization, Nodal Officer, Internship Supervisor and Mentor, Internship Mechanism and Evaluation. The present article enlightens the interns and internship organizations about all these aspects.
Keywords: Internship Categories; Structure; Credentials; Monitoring of Internship; Role of Internship Organizations; Nodal Officer; Supervisor; Mentor; Internship Mechanism and Evaluation